2020
DOI: 10.1101/2020.04.14.20064675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel approach reveals lipid metabolite reduction in nails of breast cancer patients as potential biomarker

Abstract: BACKGROUND: Molecular adaptations in intracellular and extracellular microenvironment of breast cancer cells promote pro-tumor metabolic reprogramming. Hence, metabolic reprogramming is seen as a crucial factor in various tumor hallmarks including drug resistance, invasiveness and metastasis. Among well-known metabolic features of breast carcinoma including Warburg effects, altered amino acid metabolism, lipid remodeling is considered as key factors in achieving pro-tumor microenvironment. Therefore, a better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…[63]), and proposed that this results from both local and generalized metabolic reprogramming by tumors which enhances catabolism of free amino acids. Although still in the pre-print stage at the time of our writing this review, these researchers also reported that their VTGE/Q-TOF-MS approach revealed an absence of the lipid metabolites choline, phosphorylcholine and lysophosphatidylcholine in nails form the same population of breast cancer cases [64]. Again, their small (and as-yet-unpublished) study is bolstered by the relatively well-described alterations of lipid metabolism in cancer (see for eg.…”
Section: Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…[63]), and proposed that this results from both local and generalized metabolic reprogramming by tumors which enhances catabolism of free amino acids. Although still in the pre-print stage at the time of our writing this review, these researchers also reported that their VTGE/Q-TOF-MS approach revealed an absence of the lipid metabolites choline, phosphorylcholine and lysophosphatidylcholine in nails form the same population of breast cancer cases [64]. Again, their small (and as-yet-unpublished) study is bolstered by the relatively well-described alterations of lipid metabolism in cancer (see for eg.…”
Section: Cancermentioning
confidence: 95%
“…Furosine was analyzed after hydrolysis in 6M HCl at 95°C for 30h [23], while uric acid was determined after heating in a basic solution (0.1M NaOH at 90°C for 20mins) [54,56], and steroid hormones and ethyl glucuronide were extracted by sonicating nails in methanol [90]. Min et al [59] employed a derivatization before their analysis of polyamines, while Mitruka and co-workers [62,64] developed a novel, vertical tube gel electrophoresis (VTGE) method to extract amino acids and lipid metabolites. Further purification was generally not performed, but some scientists have used solid-phase extraction plates or cartridges (eg.…”
Section: Sampling and Analytical Approachesmentioning
confidence: 99%